Esophageal microbiome signature in patients with Barrett's esophagus and esophageal adenocarcinoma. - Loris Riccardo Lopetuso; Marco Severgnini; Silvia Pecere; Francesca Romana Ponziani; Ivo Boskoski; Alberto Larghi; Gianluca Quaranta; Luca Masucci; Gianluca Ianiro; Tania Camboni; Antonio Gasbarrini; Guido Costamagna; et al. (PLoS ONE, 2020)
Preliminary studies suggested a possible correlation of microbiota with Barrett's esophagus (BE) and esophageal adenocarcinoma (EAC), where the need for tools to ameliorate its poor prognosis is mandatory. We explored the potential signature of esophageal microbiota and its predicted functional profile along the continuous spectrum from BE to EAC. We analyzed through 16S-based amplicon sequencing the mucosal microbiota and the microbiota-related functional predictions in 10 BE and 6 EAC patients compared with 10 controls, exploring also potential differences between the metaplastic mucosa (BEM) and the adjacent normal areas of BE patients (BEU). BEM and EAC showed a higher level of α and β-diversity. BEM evidenced a decrease of Streptococcus and an increase of Prevotella, Actinobacillus, Veillonella, and Leptotrichia. EAC displayed a striking reduction of Streptococcus, with an increase of Prevotella, Veillonella and Leptotrichia. LefSe analysis identified Leptotrichia as the main taxa distinguishing EAC. BEM showed a decreased α-diversity compared with BEU and a reduction of Bacteroidetes, Prevotella and Fusobacterium. Functional predictions identified peculiar profiles for each group with a high potential for replication and repair in BEM; an upregulated energy, replication and signaling metabolisms, with the fatty-acids biosynthesis and nitrogen and D-alanine pathways down-regulated in EAC. Our pilot study identifies a unique microbial structure and function profile for BE and EAC, as well as for metaplastic and near-normal areas. It proposes a new concept for BE, which could be intended not only as the histological, but, also, as the microbial closest precursor of EAC. This requires further larger follow-up studies, but opens intriguing horizons towards innovative diagnostic and therapeutic options for EAC.